2011
DOI: 10.1111/j.1467-9507.2010.00588.x
|View full text |Cite
|
Sign up to set email alerts
|

Linking Maternal Warmth and Responsiveness to Children's Self‐regulation

Abstract: The present study demonstrated that a more differentiated view of positive parenting practices is necessary in the study of children's acquisition of self-regulation. Here, the unique contributions of maternal warmth and responsiveness to distress to children's self-regulation were tested in a sample of 102 German mothers and their kindergarten children (51 girls and 51 boys). Behavior regulation and internalization of rules of conduct were examined as specific components of children's self-regulation. As expe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

8
51
1
4

Year Published

2012
2012
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 92 publications
(64 citation statements)
references
References 73 publications
(144 reference statements)
8
51
1
4
Order By: Relevance
“…It is surprising that we did not find support for an association between maternal sensitivity and inhibitory control in the current study, as a body of previous research has found such an association (Brophy-Herb et al, 2012; Lengua et al, 2007; NICHD ECCRN, 2005b; Spinrad et al, 2012; von Suchodoletz, Trommsdorff, & Heikamp, 2011). There may be a number of reasons for this.…”
Section: Discussioncontrasting
confidence: 99%
“…It is surprising that we did not find support for an association between maternal sensitivity and inhibitory control in the current study, as a body of previous research has found such an association (Brophy-Herb et al, 2012; Lengua et al, 2007; NICHD ECCRN, 2005b; Spinrad et al, 2012; von Suchodoletz, Trommsdorff, & Heikamp, 2011). There may be a number of reasons for this.…”
Section: Discussioncontrasting
confidence: 99%
“…Caregiver sensitivity, characterized by promptly responding to and correctly interpreting children’s cues (Ainsworth, Blehar, Waters, & Wall, 1978), is critical for the reduction of young children’s distress in emotionally arousing situations; caregivers who are more responsive to their children’s negative emotions may influence their children’s experience of negative emotions and create a context in which children are able to develop, employ, and practice the ability to modulate arousal (Gianino & Tronick, 1988; Kopp, 1989). A number of studies have demonstrated the influence of sensitive and supportive parenting on behavioral indices of children’s regulation and negative reactivity (e.g., Rubin, Burgess, Dwyer, & Hastings, 2003; von Suchodoletz, Trommosdoff, & Heikamp, 2011). However, fewer studies have assessed the association between parenting and physiological indices of temperament, and less is known regarding the mechanisms through which this effect takes place.…”
Section: The Effect Of Maternal Sensitivity On Parasympathetic Physiomentioning
confidence: 99%
“…In particular, parental warmth and responsiveness, defined as consistent, prompt, contingent, and appropriate reactions to the child that are supportive in quality (Bornstein, Tamis-Lemonda, Hahn, & Haynes, 2008; Landry et al, 2012; Landry, Smith, Swank, Assel, & Vellet, 2001), has been linked to behavioral regulation, compliance, and a reduced incidence of externalizing behaviors (Jones et al, 2008; Jennings et al, 2008; Rothbaum & Weisz, 1994; von Suchodoletz, Trommsdorff, & Heikamp, 2011; Wahler & Meginnis, 1997). Parental warmth might also serve as a protective factor in the presence of familial stressors.…”
mentioning
confidence: 99%